OPINIONS OF STUDENTS REGARDING THE USE OF INTERACTIVE WHITEBOARD IN LOWER SECONDARY EDUCATION - NEMCOVA, Jana (Trends in education, 2014)
The development of modern Technologies is the main causer of various changes in the field of education. These changes and innovations in the educational processes are responsible for replacing the old-fashioned green/blackboards by new modern interactive whiteboards. The article focuses on the evaluation of students´ opinions about the frequency of use of the interactive whiteboards in lower secondary education. The results from our research point at the fact that the use of interactive whiteboard has a great impact on the motivation of students as it is consistently expressed and confirmed by both students and teachers.
Keywords: interactive whiteboard; students; the frequency of use; primary schol.